Rekonstruksi Sosial Kampung Pecarikan: Upaya Pemberdayaan Masyarakat Melalui Kegiatan Positif - Ismayati, Ipah (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2024)
The Pecarikan Village is a real example of a village with a variety of social problems such as unruly garbage disposal and a low level of education. The study aims to analyze the social challenges in Kampung Pecarikan and explore initiatives for community empowerment through positive activities. Through qualitative methods, the researchers found that activities such as gotong royong, Masar, joint studies, and religious activities have had a positive impact. It is seen in the rise of gotong royong spirit, awareness of education and health, as well as harmonious inter-citizenship relations. Pecarikan Village, located in Cokopsulanjana Village, Kurung Waringin, Serang District, Banten, is characterized by multiple social issues including improper waste disposal, inadequate education, and limited access to clean water. The research aimed to analyze the social challenges in the village and investigate initiatives for community empowerment through positive activities. Research methods involve observations, interviews, and FGD. Activities like gotong royong, Masar, collaborative studies, posyandu sessions, religious practices, and community bonding events have significantly boosted the spirit of cooperation, raised awareness about education and health, and fostered harmonious community relationships.